Pravastatin treatment causes a shift in the balance of hippocampal neurotransmitter binding densities towards inhibition - Müller, Harald; Berger, Christian; Schwab, Stefan; Sommer, Clemens (Brain research, 2010)
Since pravastatin, a HMG-CoA reductase inhibitor, has recently been shown to reduce infarct volumes and glutamate release in a rat model of ischemic stroke, the aim of the present study was to investigate whether this neuroprotective effect may be due to a modulation of excitatory and inhibitory neurotransmitter receptors. Therefore, Wistar rats were treated six times in 4 days with pravastatin or saline and allowed to survive for 6 hours or 5 days (n=10 per time point and group), respectively. Using quantitative receptor autoradiography, ligand binding densities of [3H]MK-801, [3H]AMPA, and [3H]muscimol for labeling of NMDA, AMPA, and GABAA receptors were analyzed in sensorimotor cortices Par1 and Par2, the striatum, and the hippocampus. Statin therapy induced complex alterations of ligand binding densities in different brain regions. Labeling of NMDA receptors was significantly increased in Par2, both after 6 hours and 5 days, respectively. Within the striatum, AMPA as well as GABAA receptor binding values were significantly increased on day 5. Furthermore, a marked and significant increase of [3H]muscimol ligand binding to GABAA receptors throughout all hippocampal subfields was seen after 6 hours. This complexity could easily be unraveled when focusing on the balance between excitatory glutamate and inhibitory GABAA receptors, in which case only the increase of hippocampal [3H]muscimol ligand binding 6 hours after the first application of pravastatin was accompanied by a net shift towards inhibition. Consequently, our data suggest an additional regulatory pathway induced by statins, namely modification of the abundance of excitatory and inhibitory neurotransmitter receptors.
Erstmals am 22 December 2009 online veröffentlicht
Gesehen am 10.05.2023